IBADAH-IBADAH ILAHI DAN MANFAATNYA DALAM PENDIDIKAN JASMANI - Titim Fatimah (Edukasi Islami: Jurnal Pendidikan Islam, 2015)
Islamic education has memperhati comprehensive human-kan, the Islamic education in terms of human attention-faceted; spiritual terms, in terms of sense (intellectual), and enthusiastic grow well in terms of physical and appropriate, in order to carry out the tasks that have been entrusted to humans. Attention Islam in terms of physical education is a human deliver on physical health in general, and basic knowledge about health, and care of diseases. Physical education is one of the aspects of Islamic education that need attention. Moreover, physical man will be held accountable on the Day of Judgment. Worship is conducted by humans is the right of Allah, which He has created this universe with regular system and beautiful, even Allah created man with the best of shape. In worship services that have been prescribed by Allah have a positive influence on human physical educationÂ Kata Kunci: ibadah, pendidikan, jasmani